A review: Assessment of the Theories of Fundamental Mechanisms, Designing, and Failure on Structural Adhesive Joints Bond - Abdulzhra, Hayder Mohamdali; Nassar, Ameen Ahmed (Basrah Journal for Engineering Sciences, 2025)
Adhesives have been around for millennia. Nevertheless, this technique for joining has only seen significant development within the past 70 years. Professional technical engineering applications primarily use adhesives derived from synthetic polymers, a development that dates back to the mid-1940s. Its characteristics facilitate their strong adhesion to most substrates, as well as their ability to transfer substantial loads. This paper presents an extensive assessment of the current knowledge in the field of adhesives and related technologies, with a focus on adhesion theories and their parameters, as well as designing, joint configuration, geometric aspects, and failure modes. The paper also explores the interplay between research and development efforts, industrial standards, and regulatory aspects, with the goal of fostering collaboration between academia and industry. Over the past years, the development of new materials, methods, and models has resolved many of the shortcomings. Nonetheless, it is still possible to evaluate and estimate the optimal combination of aspects that will give the greatest efficiency and performance for adhesive bond joints (ABJs).